PHYSICAL AND CHEMICAL CHARACTERIZATION OF PEAT WATER AT TANJUNG JABUNG BARAT, JAMBI PROVINCE - Yulia Morsa Said; Yudi Achnopa; Wahyudi Zahar; Yudha Gusti Wibowo (Jurnal Sains & Teknologi Lingkungan, 2019)
Clean water is a problem in peat area. Low water quality in peat land area have characteristic brown till black in color, low pH, high heavy metals content that cannot use to daily activities. Tungkal Ilir, Tanjung Jabung in Jambi Province is a place that have low quality in water resources caused by peat. High Total suspended solid (TSS), Total Dissolved Solid (TDS), Conductivity (DHL), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), low pH and high heavy metals are parameters in wastewater in there. This paper will describe physical and chemical parameters on peat water clearly, systematic and give alternative solution to solve this problem.